FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH ASURANSI DALAM MEMILIH PRODUK KESEHATAN PADA PT. ASURANSI PRUDENTIAL SYARIAH CABANG BINJAI - Yudistira, Yudistira (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2021)
This study aims to determine the effect of customer’s knowledge, motivation, and promotion towards the choice of health insurance products at PT Asuransi Prudential Syariah Branch Binjai. The data in this research is used by collecting 34 quetioners of insurance customers. And then the data is processed and analysed. In this research, quantitative methode is used to know the effect, so multiple linear regression analysis, t-test, F-test, and determinant analysis are used. Based on the research, the result is customer’s knowledge has no effect towards the choice of health insurance products, motivation has a effect towards the choice of health insurance products, and promotion has a effect towards the choice of health insurance products. Based on F-test the result is the value of Fhitung is 4,959. The value of Fhitung is more than the value of Ftable 2,922, so it can be know that customer’s knowledge, motivation, and promotion simultaneously have a significant effect towards the choice of health insurance products at PT Asuransi Prudential Syariah Branch Binjai.